Analisis Penerapan Pembelajaran IPAS Kontekstual Berbasis Lingkungan Sekitar pada Siswa Kelas V SDN 17 Pekanbaru - Aldi Pratama; Dea Mustika (YASIN, 2026)
Natural and Social Sciences (IPAS) learning in elementary schools continues to face challenges in connecting learning materials with students’ real-life experiences. This study aimed to analyze the implementation of contextual IPAS learning based on the surrounding environment among fifth-grade students at SDN 17 Pekanbaru. The study employed a qualitative descriptive approach involving four fifth-grade teachers and six students from Class V-D as informants. Data were collected through observation, interviews, and documentation from August 10 to 13, 2026, as part of a research process conducted from December 2025 to August 2026. Data trustworthiness was examined through triangulation, while data analysis involved data condensation, data display, and conclusion drawing and verification. The results showed that seven components of contextual learning—constructivism, inquiry, questioning, learning community, modelling, reflection, and authentic assessment—had been implemented in IPAS learning. Teachers connected the material with students’ experiences, utilized the school environment, including family medicinal plants (TOGA), and facilitated observation, question-and-answer sessions, group discussions, demonstrations, reflection, and the assessment of both learning processes and outcomes. However, the implementation was not entirely consistent because of limitations in time, learning media, and planning. This study concludes that contextual IPAS learning based on the surrounding environment has been implemented and has the potential to create more active and meaningful learning. These findings imply the need for school support in strengthening planning, providing learning media, and enhancing teacher capacity to ensure that the surrounding environment is utilized systematically in learning.